Neutron monitors and muon detectors for solar modulation studies: 2. ϕ time series. Issue 4 (15th August 2017) - Ghelfi, A.; Maurin, D.; Cheminet, A.; Derome, L.; Hubert, G.; Melot, F.
Abstract: The level of solar modulation at different times (related to the solar activity) is a central question of solar and galactic cosmic-ray physics. In the first paper of this series, we have established a correspondence between the uncertainties on ground-based detectors count rates and the parameter ϕ (modulation level in the force-field approximation) reconstructed from these count rates. In this second paper, we detail a procedure to obtain a reference ϕ time series from neutron monitor data. We show that we can have an unbiased and accurate ϕ reconstruction ( Δ ϕ / ϕ ≃ 10 % ). We also discuss the potential of Bonner spheres spectrometers and muon detectors to provide ϕ time series. Two by-products of this calculation are updated ϕ values for the cosmic-ray database and a web interface to retrieve and plot ϕ from the 50's to today (http://lpsc.in2p3.fr/crdb ).